Identifikasi Isu Pendidikan Islam di Era Global: Pengaruh Globalisasi pada Profesi Guru - Sukari, Sukari; Ahmada, Futiha Alambarra Amaan (Lembaga Yasin AlSys, 2024)
The era of globalization, which has shaped the modern world, has influenced the education sector with various issues that have significantly transformed society, schools, educators, and students. In the Islamic education sector, globalization presents unique challenges for educators or teachers to demonstrate the relevance of Islamic educational institutions, which emphasize the inculcation of religious values and the development of noble character in their students. To understand the changes and issues affecting Islamic education and to identify the impact of globalization on teachers, this article is compiled using a literature review approach to provide broad and comprehensive descriptive results. From the exploration of several sources and literature, it is found that there are several challenges faced by Islamic education in the global era, such as conformism, the dichotomy between faith-based and scientific knowledge, changes in educational orientation, as well as moral and personality crises. These challenges urge teachers to continually be able and ready to equip themselves with a correct and profound understanding of religion, along with mastery of science and technology, in order to keep pace with the advancement of an information-based and digital society. This can be achieved by instilling the right understanding and practice of Islamic values while being adaptive, responsive, and innovative in addressing changes, namely by balancing globalization with the correct acquisition of knowledge and the use of technology for educational development.